The accuracy of fully automated algorithms for surveillance of healthcare-onset Clostridioides difficile infections in hospitalized patients - Suzanne Desirée van der Werff; Mikael Fritzing; Hideyuki Tanushi; Aron Henriksson; Hercules Dalianis; Anders Ternhag; Anna Färnert; Pontus Nauclér (Cambridge University Press, 2022)
We developed and validated a set of fully automated surveillance algorithms for healthcare-onset CDI using electronic health records. In a validation data set of 750 manually annotated admissions, the algorithm based on International Classification of Disease, Tenth Revision (ICD-10) code A04.7 had insufficient sensitivity. Algorithms based on microbiological test results with or without addition of symptoms performed well.